(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
This paper investigates the cognitive mechanisms underlying the development of auxiliary verbs across languages, arguing that conceptual metonymy plays a central role in their grammaticalization. While previous studies have primarily emphasized metaphor as the driving force behind semantic extension, this research demonstrates that metonymy—based on contiguity within the same conceptual domain—provides a more accurate explanation for the emergence of auxiliary and supportive verb constructions. The study analyzes data from Uzbek, English, Russian, Chinese, and Japanese, revealing that auxiliary verbs originate from lexical verbs through systematic metonymic shifts. The findings suggest that the transition from lexical meaning to grammatical function reflects universal cognitive patterns rather than language-specific phenomena.